Comparative analysis of the criminal legislation of foreign countries about criminal liability for threat the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
In this article, the concept of criminal responsibility for the threat is one of the fundamental concepts and discussion of law. There is a view in which the criminal responsibility for the threat is seen as a means of criminal law, through the tools. Doing an analysis of foreign countries, we can understand the threat of greater than supposed. A comparative analysis shows that in some countries, the threat – it’s just an act, while others pay special significance threats to validity and differentiation of criminal responsibility for it and assigns it to the category of crimes.Key words: threat, criminal offense, criminal liability, comparative analysis, the сriminal сode, punishment.